Experimental Evaluation of a Youth Dating Violence Prevention Program in New York City Middle Schools, 2009-2010 - Taylor, Bruce ([Verlag nicht ermittelbar], 2012)
The study sought to measure knowledge about laws related to domestic violence and harassment, resources for help, rape myths, and skills such as conflict resolution; attitudes about the acceptability of violent, abusive, and harassing behaviors; behavioral intentions to avoid committing violent acts in the future as well as intentions to intervene when in the position of a bystander; behavioral measures about peer and dating partner physical and sexual violence experienced as a victim or perpetrator, and sexual harassment experienced as a victim or perpetrator; and other items covering a demographic profile of the students and questions on prior attendance at an educational program about sexual assault, harassment, or violence, and prior history of dating.Researchers randomly assigned a school-based intervention to 6th and 7th grade classes (over 2,500 students) in 30 public middle schools in New York City to one of four conditions: (1) a classroom-based intervention; (2) a school-wide intervention; (3) interventions that included both classroom and school-wide components; or (4) a (no treatment) control group. The classroom based intervention was delivered through a six session curriculum that emphasized the consquences for perpetrators of domestic violence and harassment, state laws and penalties for domestic violence and harassment, the construction of gender roles, and healthy relationships. The school-wide intervention included the development and use of temporary school-based restraining orders, higher levels of faculty and security presence in areas identified by students and school personnel as unsafe "hot spots", and the use of posters to increase awareness and reporting of domestic violence and harassment to school personnel. Pencil and paper surveys were distributed to students at three different times: (1) immediately before the assignment to one of the four study conditions, (2) immediately after the treatment (or control condition) was completed, and (3) between five and six months after assignment to one of the four study conditions. The surveys took about 40 minutes to complete and were completed in the classroom during one class period.